اثبات جرائم میں عصری قرائنی شہادت کی اہمیت اور اسلامی تعلیمات: Role of importance of Circumstantial Evidence in Crimes Proof in Islamic Perspective - Dr. Ghulam Farooq; Dr. Muhammad Waris Ali (MEI, 2022)
There are numerous in Quran and Sunnah about the justification of circumstantial evidence. Holy Prophet used Circumstantial evidence on the base of his supposition, and also it is secondary evidence but it has not obtained the status Primary evidence . As the Circumstantial evidence and DNA report is not accepted as primary evidence that is why Islamic Fiqh demands visual evidence as well. That is why that required of visual evidence is necessary in Islam .However it can be taken as omen based evidence ,secondary evidence and circumstantial evidence. And if the Court is satisfied, the penalty can be imposed. In America and other Western countries DNA repot is accepted as evidence for punishment. But our experts of jurisprudence accept circumstantial evidence just as secondary evidence.